2022
DOI: 10.1111/ppl.13778
|View full text |Cite
|
Sign up to set email alerts
|

How does UV‐B stress affect secondary metabolites of Scutellaria baicalensis in vitro shoots grown at different 6‐benzyl aminopurine concentrations?

Abstract: Ultraviolet‐B (UV‐B) radiation is one of the abiotic stresses that can significantly affect the secondary metabolite accumulation in in vitro tissue cultures of medicinal plants. The present study investigated the effects of UV‐B radiation on the secondary metabolites and antioxidant activities of Scutellaria baicalensis in vitro shoots grown at different concentrations of 6‐benzyl aminopurine (6‐BA), which is the cytokinin most widely used in plant tissue culture. The UV‐B radiation caused significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The malondialdehyde (MDA) content was determined according to Yun et al (2022). Fresh samples (0.5 g) were well grounded in 5 mL of 10% trichloroacetic acid (TCA).…”
Section: Methodsmentioning
confidence: 99%
“…The malondialdehyde (MDA) content was determined according to Yun et al (2022). Fresh samples (0.5 g) were well grounded in 5 mL of 10% trichloroacetic acid (TCA).…”
Section: Methodsmentioning
confidence: 99%
“…Second, the accumulation of secondary metabolites in S. baicalensis is associated with abiotic stress. Ultraviolet-B (UV-B) radiation can significantly affect the accumulation of secondary metabolite aglycones (including baicalein, wogonin and scutellarein) in tissue culture and produce oxidative stress (Yun et al 2022 ). Yuan et al found that abnormal temperature (10 °C and 40 °C) reduced the content of flavonoids in S. baicalensis , and high temperature affected the synthesis of two key enzymes, 7-O-glucuronosyltransferase and β-glucuronidase, in the interconversion of baicalin and baicalein (Yuan et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%